Theoretical study of the interaction of fluorinated dimethyl ethers and the ClF and HF molecules. Comparison between halogen and hydrogen bonds. Issue 9 (18th February 2016) - Sutradhar, Dipankar; Chandra, Asit K.; Zeegers‐Huyskens, Thérèse
Abstract : A theoretical study of the halogen‐bonded complexes formed between fluorinated dimethyl ethers ( n F  = 0–4) and ClF is carried out using the wB97XD method combined with the 6‐311++G(d, p) basis set. The properties of the complexes are compared with the corresponding properties of the hydrogen‐bonded complexes formed between the same electron donors and HF. The optimized geometries, the interaction energies, relevant natural bonding orbital characteristics along with some vibrational data are calculated. The analyzed properties also include the symmetry adapted perturbation theory decomposition of the energies along with the atoms‐in molecule analysis. For both the halogen and hydrogen bonds, the interaction energies are ruled by the intermolecular hyperconjugation energies. In contrast, the correlations between the binding energies and the basic properties of the ethers or the charge transfer are different for the halogen and hydrogen bonds. The applicability of the Bent's rule to these systems is discussed. © 2016 Wiley Periodicals, Inc. Abstract : Fluorinated ethers are potential replacement for the hazardous chlorofluorocarbons as they lack ozone depletion potential and can also perturb intermolecular interactions through hydrogen bonds and van der Waals interaction without forming or breaking covalent bonds. Non‐covalent interactions such as hydrogen and halogen bond have also been used to control the molecular packing. The comparison between the two interactions has gathered much attention as halogen bond exhibits similar properties and applications to hydrogen bonds.